The Effect of Price and Product Variety on Purchasing Decisions (Mixue Ringin Contong Jombang) - Faruq Syafiq, Muhammad (Program Studi Ekonomi Islam, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng, 2026)
This study aims to analyze the influence of price and product variety on consumer purchasing decisions at Mixue Ringin Contong Jombang. The research employed a quantitative approach using descriptive and associative methods. The sampling technique used was accidental sampling with a total of 100 respondents who were consumers of Mixue Ringin Contong Jombang. Data were collected through questionnaires, observations, and interviews. Data analysis was conducted using validity tests, reliability tests, and multiple linear regression analysis with the assistance of IBM SPSS version 26. The results showed that all research instruments were valid and reliable. The multiple linear regression analysis indicated that the price variable had a regression coefficient of 0.162 and the product variety variable had a coefficient of 0.196, indicating that both price and product variety positively influence consumer purchasing decisions. Product variety was found to have a more dominant influence than price. The findings suggest that companies should pay attention to pricing strategies and product diversity in order to improve consumer purchasing decisions for Mixue Ringin Contong Jombang products.